Differentiating features of Benign vs. Malignant Phyllodes Tumours: a case series - Haroon, Raihanah; Che Mohamed, Siti Kamariah; Shaharuddin, Nur Adilah (2022)
Introduction: Phyllodes tumours of the breast, first dubbed cystosarcoma phyllodes are rare fibroepithelial tumours, accounting for less than 1% of all breast neoplasms. The World Health Organization (WHO) classified these tumours into three categories, i.e benign, borderline and malignant based on histopathological features. Benign phyllodes tumour comprised most of the tumours (35-64%), whereas the incidence of malignant phyllodes tumour is 25%. Imaging features of benign phyllodes tumour include well-circumscribed margin and homogenous echotexture, whereas malignant phyllodes tumour often demonstrate irregular margin, intratumoral cystic spaces, heterogenous echotexture and internal vascularity. Case Series: We present 4 cases of female patients initially presented with breast lump. Histopathological examination of the first two cases is malignant phyllodes tumour with background of fibrocystic changes. The first case is a 46-year-old lady whose mammogram showed a well-defined equal-density lesion. Ultrasound showed a lobulated mass, partially circumscribed margin, heterogenous internal echo and intratumoral cystic spaces. The second case is a 36-year-old lady with a high-density lesion associated with multiple dystrophic calcifications on mammogram. Ultrasound showed a heterogenous mass with irregular margin and posterior shadowing. The third and fourth cases are histopathologically confirmed as benign phyllodes tumour. The third case is a 46-year-old lady whose mammogram showed an equal density lesion while sonography revealed a well-defined oval lesion with heterogenous echotexture but no intralesional cystic spaces. Another case is a 46-year-old lady with a high-density lesion on mammogram while sonographically showed a well-defined, lobulated lesion with heterogenous echotexture and intralesional cystic spaces. Conclusion: In conclusion, benign and malignant phyllodes tumours manifest several differentiating features sonographically though some of the features may overlap. Lesion margin, internal echoes and vascularity as well as presence of liquefaction may help to identify different pathological grades of phyllodes tumour. This is crucial due to diverse potential for recurrence and metastasis.